Mapping The Eye Tracking Application To Assess Students’ Metacognitive Skills In Chemistry Learning - Khairiatul Muna; Muhammad Bahit (Tarbiyah : Jurnal Ilmiah Kependidikan, 2026)
Metacognitive skills impact learning in a variety of significant and tangible ways, including problem solving. A method that may be employed to assess problem-solving and metacognitive skills is the eye tracking method. The purpose of this research is to conduct systematic analysis and to map the application of eye tracking in chemistry learning, including its relationship to metacognition and problem-solving skills. Thus, it is anticipated that a greater comprehension of how to use the eye tracking and how it has been applied. This research was conducted using the bibliometric method with the assistance of Publish or Perish (PoP), Zotero, and VOSviewer software. The analysis of the data was conducted qualitatively and quantitatively descriptively. Fifty-five (55) articles were analyzed through the utilization of VOSviewer. The results indicate that there is a scarcity of Scopus-indexed journal articles that detail research on the application of eye tracking for assessing metacognitive skills in chemistry learning (in one study). It is therefore imperative to undertake additional research and disseminate the findings. The primary objective of additional research is to ascertain the efficacy of eye tracking. The findings of the analysis also yielded a comprehensive synopsis of the procedures employed in eye tracking for educational purposes, encompassing both chemistry and non-chemistry domains. Additionally, eye tracking has the capability to systematically and comprehensively delineate, examine, and define the learning process, encompassing the application of metacognitive skills in problem solving and learning.